Production of human norovirus protruding domains in E. coli for X-ray crystallography - Leuthold, Mila; Koromyslova, Anna D.; Singh, Bishal; Hansman, Grant S. (JoVE. Video journal, 2016)
The norovirus capsid is composed of a single major structural protein, termed VP1. VP1 is subdivided into a shell (S) domain and a protruding (P) domain. The S domain forms a contiguous scaffold around the viral RNA, whereas the P domain forms viral spikes on the S domain and contains determinants for antigenicity and host-cell interactions. The P domain binds carbohydrate structures, i.e., histo-blood group antigens, which are thought to be important for norovirus infections. In this protocol, we describe a method for producing high quality norovirus P domains in high yields. These proteins can then be used for X-ray crystallography and ELISA in order to study antigenicity and host-cell interactions. The P domain is firstly cloned into an expression vector and then expressed in bacteria. The protein is purified using three steps that involve immobilized metal-ion affinity chromatography and size exclusion chromatography. In principle, it is possible to clone, express, purify, and crystallize proteins in less than four weeks, which makes this protocol a rapid system for analyzing newly emerging norovirus strains.